Evaluation of the cranial base deflection. A cephalometric study - Flores Angeles, Adara (2017)
Objective: To evaluate the cranial base deflection in different skeletal class patients. Materials and method: Descriptive and retrospective study included cephalometric radiographs of 318 Peruvian children, with an age range from 6 to 12 years selected from the School of Dentistry at San Marcos University and the Orthodontics and Maxillofacial Orthopedics Department at Children’s National Health Institute taken between 2000 and 2015. Cranial base deflection was evaluated taking NSBa angle as a reference and compared with the three skeletal classes taking ANB angle as a reference. Sex and age were also compared. Results: Cranial base deflection value was 132°± 4.85°. In Class I group it was 132.23°±5°, in Class II group: 132.21°±4.81° and in Class III group: 130.23°±4.29° (significant differences were found p < 0.05). Cranial base deflection in females was 131.9°±4.86° and 132°±4.87°in males (no significant differences were found p = 0.831). In 6 year-old patients the deflection value was 130.80°±4.44° while in the 12 year-old group was 129.76°±3.05° (No significant differences were found p = 0.275). Conclusions: The cranial base deflection is similar in Class I and Class II Peruvian children but different in Class III.